Anti-Freeze Stabilizer System Based On Azidated Glycerol For Natural Rubber Latex - Abd Samat, Siti Nuraya (2022)
Natural rubber latex (NRL) normally transported to any destination in colloid / liquid form. It requires large storage containers such as drums and the probability of latex leakage during transportation to happen is higher. To prevent the latex spillage, the liquid form of NRL was transform into solid / frozen latex by freezing method. However, negatively charged protein layer that stabilized NRL particles may be broken by ice crystals during freezing and these destabilized NRL particles will form big lump after thawing. So, this study proposed a new low temperature of stabilizer named azidated glycerol (AG) that will be incorporated in NRL liquid before freezing process. It is expected that AG able to act as colloid stabilizer thus preventing the coalescence of rubber participles from occurring after thawing. AG was prepared by a chemical reaction of pure glycerol with sodium azide. The resulting AG was then added into NRL colloid as an anti-freeze stabilizer to prevent the rubber latex particles from coalesces at a lower temperature. NRL containing AG was then freeze at a temperature of -4 °C. After 24 hours of freezing, the frozen latex was thaw at ambient temperature for 1 hour followed by heating in a water bath at 40 °C for another 1 hour.